A Guide to college programs in hospitality and tourism a directory of CHRIE member colleges and universities. - Council on Hotel, Restaurant, and Institutional Education (U.S.). (New York, N.Y. Wiley, 1993)
Annual
Continues: Guide to hospitality and tourism education.
Keywords: Hospitality industry -- Study and teaching (Higher) -- United States -- Directories; Hospitality industry -- Study and teaching (Higher) -- Directories; Tourist trade -- Vocational guidance -- Directories; Tourist trade -- Vocational guidance -- United States -- Directories; Universities and colleges -- Directories; Universities and colleges -- United States -- Directories